PENGARUH MEDIA PEMBELAJARAN FLASHCARD TERHADAP KEMAMPUAN MEMBACA SISWA KELAS II SEKOLAH DASAR - Sagita Aprilia; Uci Ulfa Nur’afifah; Budi Rachman (STKIP Subang, 2025)
This study aims to examine the effect of flashcard learning media on the readingability of second-grade students at SDN Pelang Lor 1. The research uses aquantitative approach with a pre-experimental design and the One Group Pre-testand Post-test method. The sample consisted of 30 students selected throughsaturated sampling. Data were collected through observation and reading abilitytests conducted before and after the treatment. The results of paired sample t-test showed a significant increase in post-test scores (mean = 88.00) compared to pre-test scores (mean = 61.04), with a significance value of 0.000 < 0.05. This indicates that flashcard media has a significant effect on improving students’reading ability. The findings support previous research which confirms theeffectiveness of visual media in early reading skills. Flashcards are proven to bean effective, interactive, and enjoyable tool that suits the characteristics ofelementary students in early grades.